Monetary policy, inflation outlook, and recession probabilities - Andrea Ajello; Luca Benzoni; Makena Schwinn; Yannick Timmer; Francisco Vazquez-Grande (Federal Reserve Bank of Chicago, 2022)
Why does the short-term slope of the yield curve predict recessions? We explore the economic forces underlying Treasury yields' fluctuations and highlight the roles of a tight monetary policy stance and expectations of lower inflation in predicting downturns. While the monetary policy stance is still accommodative, indicating a low recession probability, the negative inflation slope points to higher odds of a recession within a year. An aggressive removal of policy accommodation increases the recession probability to 60%.
Keywords: G10; G12; E32; E37; E44; E52; 330; yield-curve slope; recession forecasts; monetary policy; bond risk premia; policy path; inflation forecasts; near-term forward spread